Hazard and vulnerability in urban inundated underground space: Hydrodynamic analysis of human instability for stairway evacuation. (15th February 2022) - Li, Qijie; Xia, Junqiang; Xie, Zhihua; Zhou, Meirong; Deng, Shanshan
Abstract: Underground flooding events are being exacerbated due to the rapid expanding of underground space in urban and the extreme precipitation events by climate change. It is increasingly necessary to study hydrodynamics and instabilities of human on staircases in the flood-prone underground space for risk identification and disaster reduction. However, the turbulent complexity and complicated fluid-human interaction still challenge the study of flow structure and the calibration of human instability model. In this work, a hydrodynamic model coupled with the mechanics-based method was proposed to study fluid-human interactions and hazard risks on flooding stairways. Numerical validations show that the model can obtain reliable solutions of flow characteristics on staircases. It is found that there exists a jet flow downstream the rest platform and the critical region after the 3rd step downstream the platform is identified as a high risk area to cause sliding instability. The risk of sliding instability for a child is higher than that for an adult in jet flow region. In addition, results show that the downstream vortical flow structure and turbulent effect are obviously enhanced because of the interdict of jet flow by the human obstacle.